CoVITEST: A Fast and Reliable Method to Monitor Anti-SARS-CoV-2 Specific T Cells From Whole Blood - Egri, Natalia; Olivé, Victoria; Hernández-Rodríguez, José; Castro, Pedro; De Guzman, Catherine; Heredia, Libertad; Segura, Ana Castellet; Fernandez, M. Dolores; de Moner, Noemi; Torradeflot, María; Ballús, Judit; Martinez, Robert; et al. (Frontiers in Immunology, 2022)
The cellular and humoral immune responses are essential towards COVID-19 recovery and protection against SARS-CoV-2 reinfection. To this day, the evaluation of the immune protection to SARS-CoV-2 has mainly been focused on the detection of antibodies, generally disregarding the cellular response, or placing it as a secondary element. This phenomenon is probably explained by the complex nature of the assays needed to analyze the cellular immunity, opposed to the technically simple and automated detection of antibodies. Nevertheless, a large body of evidence supports the relevance of T cells for the protection against SARS-CoV-2, especially in vulnerable patients. Here we propose CoVITEST (Covid19 anti-Viral Immunity based in T-cells for Evaluation in a Simple Test); a fast, affordable and scalable assay to detect reactive T-cells, which delivers accurate results in under 8 hours The assay was used to evaluate different cohorts including vaccinated individuals (n = 30) and convalescent COVID-19 donors (n =51), in a side-by-side comparison against gold standard IFN-γ ELISpot. We show that our CoVITEST is quicker and simpler, but the results are comparable to the time-consuming ELISpot In conclusion, we present a simple but reliable assay to detect cellular immunity against SARS-CoV-2, which may be used during this pandemic to monitor vulnerable patients, such as those pharmacologically immunosuppressed, for an adjusted care.